Changes in G-Actin after Platelet Activation in Platelet Rich Plasma - Heptinstall, S; Glenn, J; Spangenberg, P (Thrombosis and Haemostasis, 1992)
We have used the DNase I inhibition assay to study changes in G-actin after platelet activation in platelet-rich plasma (PRP) induced by ADP. Because of problems associated with depolymerization of F-actin after lysis of ADP-activated platelets in the presence of plasma, G-actin was measured using a lysis buffer that contained formaldehyde to prevent any depolymerization of F-actin.Different patterns of response were seen depending on the concentration of ADP used, and these were modified by avoiding aggregation by either not stirring the sample or by adding EDTA. The results show rapid conversion of G-actin to F-actin in association with shape change, and there is a further decrease in G-actin associated with irreversible platelet aggregation. Thus evidence is presented that actin polymerization occurs in two phases after ADP stimulation.